IMPROVING STUDENTS' VOCABULARY MASTERY OF CLASS IIA THROUGH THE USE OF INTERACTIVE LEARNING MEDIA WORDWALL AT SD INPRES BUMI SAGU - Muh Rizal; Ni Kadek Devy Rafika; Sin Dinayanti Laudea (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The This research was conducted at SD Inpres Bumi Sagu, motivated by the problem of low vocabulary mastery among IIA grade students. This study aims to: (1) describe the use of Wordwall interactive learning media in Class IIA, (2) describe the improvement of vocabulary mastery of Grade IIA students, and (3) examine the effect of Wordwall interactive learning media in improving vocabulary mastery of Grade IIA students. This study used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model. The research subjects were 30 students of class IIA SD Inpres Bumi Sagu. Data were collected through observation, tests, and documentation, then analyzed descriptively qualitatively and quantitatively. The results showed (1) the use of Wordwall interactive learning media in class IIA went very well, with significant improvements from cycle I to cycle II, (2) the vocabulary mastery of IIA grade students showed significant improvement after the use of Wordwall media, (3) there was a positive effect of Wordwall interactive learning media in improving vocabulary mastery of IIA grade students, as evidenced by an increase in average scores and percentage of student learning completeness.